Consumer behavior towards Tunku Abdul Rahman Parks at Manukan and Sapi island / Susanna Ismail - Ismail, Susanna (2009)
Today, parks are emerging as one of most important spaces. They are multi-purpose public spaces that offer social, economic and environmental benefits. The Tunku Abdul Rahman Park comprises of a group of five island Pulau Manukan, Pulau Mamutik, Pulau Sapi, Pulau Sulug and Pulau Gaya. The Tunku Abdul Rahman Park is popular for activities such as sunbathing, swimming, snorkeling, diving, barbeque, bird-watching, nature walks along guided forest and mangrove trails, beach fishing (only hook and line permitted), outdoor camping (only on Sapi and Mamutik, with prior permission from the Sabah Parks office or the Park Ranger at the islands. Consumer behavior is the study of how people buy, what they buy, when they buy and why they buy. In order to fulfill customer needs and wants marketer or the organization should do some observation and what is individual's perception of what is out there of what has taken place because consumers perceptions can affects their actions, their buying habits, their leisure habits and so forth because individuals make decisions and take actions based on what they perceive to be reality and it is important that organization to understand the whole notion of perception so that they can readily determine what factors influence consumer to buy.